Biomass and carbon stock in Jatropha curcas L - Torres, Carlos Moreira Miquelino Eleto; Jacovine, Laércio Antônio Gonçalves; Toledo, Diego de Paula; Soares, Carlos Pedro Boechat; Ribeiro, Sabina Cerruto; Martins, Maria Cristina (CERNE, 2011)
This study aims to quantify the biomass and carbon stock in a crop of physic nut Jatropha curcas in Viçosa-MG at age three years. For biomass quantification, the direct or destructive method was applied to sample plants selected according to height, crown diameter and number of branches. For the determination of dry biomass in the field, the proportionality method was used. The determination of total carbon content was done in the Laboratory of Forest Soils of the Federal University of Viçosa, and the estimation of CO2 equivalent was based on the 3.67 factor. The carbon stock found in the third year of cultivation was 4.182 tC.ha-1 (15.349 tCO2-e.ha-1) and the mean annual increment (MAI) was 1.394 tC.ha-1.year-1. Results revealed that the potential carbon increment in the physic nut crop is similar to values found in other crops and natural forests yet lower than in eucalyptus crops.

No presente estudo, objetivou-se quantificar a biomassa e o estoque de carbono da cultura de Jatropha curcas no município de Viçosa - MG aos três anos de idade. Para a quantificação da biomassa foi utilizado o método direto ou destrutivo, aplicado às plantas-amostras selecionadas segundo medidas de altura, diâmetro de copa e número de ramos. A determinação da biomassa seca no campo foi obtida pelo método da proporcionalidade. O teor de carbono total foi determinado no laboratório de solos florestais da Universidade Federal de Viçosa e a estimativa do CO2 equivalente pelo fator 3,67. O estoque de carbono encontrado para o terceiro ano da cultura do pinhão manso foi de 4,182 tC.ha-1 (15,349 tCO2-e.ha-1) e o incremento médio anual (IMA) de 1,394 tC.ha-1.ano-1. Os resultados encontrados evidenciam que a cultura apresenta um incremento potencial de carbono próximo à outras culturas e às florestas naturais, entretanto, abaixo de plantios de eucalipto.
Keywords: Carbon credits; Carbon sequestration; Physic nut